Две половинки: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2017)
Экземпляры: аб. ЦБ (2018.14.03) / Инвентарный номер: 4162 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 60 / ГРНТИ: 17.82 / ББК: 84(2Роc=Рус)6